10.52931/icirpe2021 The Role of Management Control Systems In Reduce Waste And Implications to Financial Performance - Siti Hamidah Rustiana, Mahmud Gandin (International Conference on Industrial Revolution for Polytechnic Education, 2021)
The purpose of this study was to see the extent to which the role of management control system to waste and its implications for financial performance on flexible packaging company in Indonesia especially those located on the island of Java. Waste reduce the variables that affect the cost elements in this case the cost of goods sold. With good control of waste expected cost of production related to the production process of getting down and ultimately financial performance such as gross profit margin will increase. Waste can be defined as anything that adds to the time and cost of making a product but do not add value to the product from the process of transformation of inputs into outputs therefore need to be eliminated. All of these activities is a waste to extend the production process (production lead time). Associated with seven types of waste that are most common in industrial packaging is overproduction, inventory, overprocessing, and defect therefore the role of management control system becomes very important to implement and run as effectively and efficiently as possible in order to minimize waste that is because if the waste can be reduced then profit by itself will increase and ultimately financial performance will be better. This study used data from 107 respondents were 107 flexible packaging company in Indonesia, located on Java Island, while an analytical technique used is path analysis using IBM SPSS software version 20. From the data processing result that management control systems and a significant positive effect to waste, on the other side, and waste management control system simultaneously also affects positively and significant to financial performance, while waste is positive but not significant effect on financial performance as well as management control systems but not significant positive effect on financial performance.